Temporal relationships between speech and hand gestures in the vicinity of potential turn boundaries in German and Swedish conversation - Margaret Zellers; Jan Gorisch; David House (Language and Cognition, 2025)
Both gesture and talk are basic building blocks of face-to-face conversation. In this study, we address the temporal dynamics of hand gesture phases relative to places and types of turn transition. We annotated gesture features and measured temporal aspects of gesture related to speech in two languages, German and Swedish. We found variation in the temporal relationships of gesture types and alignment of gesture phases that relate to the management of turn-taking in conversation. Specifically, the frequency of different gesture phases accompanying the offset of speech differed depending on whether the same speaker held the floor or whether a new speaker took up a turn. In addition, we found that differences in temporal alignment of gesture phases can distinguish between the type of turn transition that is upcoming up to a second before the place of transition is reached. Our results emphasize the importance of the interaction of the verbal and the gestural modality to maintain the smooth flow of conversation.